1446Forgoing needed medical care among long-term survivors of childhood cancer: Racial/ethnic-insurance disparities. (2nd September 2021) - Lindsey, Lauren; Baedke, Jessica; James, Aimee; Huang, I-Chan; Ness, Kirsten; Howell, Carrie; Brinkman, Tara; Bhakta, Nickhill; Ehrhardt, Matthew; Im, Cindy; Letsou, William; Liu, Qi; et al.
Abstract: Background: Among adult childhood cancer survivors, the relationship between race/ethnicity and health insurance status, as a contributor to disparities in healthcare utilization, is poorly understood. Methods: We examined racial/ethnic-related disparities by insurance status in "forgoing needed medical care in the last year due to finances" using 3, 964 adult childhood cancer survivors (3310 non-Hispanic/Latinx White, 562 non-Hispanic/Latinx Black, and 92 Hispanic/Latinx) participating in the St. Jude Lifetime Cohort Study (SJLIFE). Multivariable logistic regression analyses, guided by Andersen's Healthcare Utilization Model, were adjusted for "predisposing" (age, sex, childhood cancer diagnosis, cancer treatment, surgery, and treatment era) and "need" (perceived health status) factors. Additional adjustment for income/education and chronic health conditions was considered. Results: The risk of forgoing care was highest among non-Hispanic/Latinx Blacks and lowest among Hispanics/Latinxs for each insurance status. Among privately-insured survivors, relative to non-Hispanic/Latinx Whites, non-Hispanic/Latinx Blacks were more likely to forgo care (adjusted OR: 1.82, 95% CI: 1.30–2.54): this disparity remained despite additional adjustment for income/education (adjusted OR: 1.43, 95% CI: 1.01–2.01). In contrast, publicly-insured survivors, regardless of race/ethnicity, had similar risk of forgoing care as privately-insured non-Hispanic/Latinx Whites. All uninsured survivors had high risk of forgoing care. Additional adjustment for chronic health conditions did not alter these results. Conclusions: The findings of this study show that provision of public insurance to all childhood cancer survivors may diminish racial/ethnic disparities in forgoing care that exist among the privately-insured and reduce the risk of forgoing care among uninsured survivors to that of privately-insured non-Hispanic/Latinx Whites. Key messages: Providing publicly funded health insurance coverage to childhood cancer survivors can reduce disparities in forgoing medical care.